2021
DOI: 10.1158/1535-7163.mct-20-0654
|View full text |Cite
|
Sign up to set email alerts
|

PLK1 and NOTCH Positively Correlate in Melanoma and Their Combined Inhibition Results in Synergistic Modulations of Key Melanoma Pathways

Abstract: Melanoma is one of the most serious forms of skin cancer, and its increasing incidence coupled with nonlasting therapeutic options for metastatic disease highlights the need for additional novel approaches for its management. In this study, we determined the potential interactions between polo-like kinase 1 (PLK1, a serine/threonine kinase involved in mitotic regulation) and NOTCH1 (a type I transmembrane protein deciding cell fate during development) in melanoma. Employing an in-house human melanoma tissue mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…In addition, knockdown of PLK1 resulted in decreased clonal survival, cell cycle arrest, and apoptosis in melanoma cells. Su et al 42 reported that higher PLK1 levels were associated with worse OS and disease-free survival (DFS), which is consistent with our results. In addition, Deeraksa et al 45 demonstrated that PLK1 expression is elevated in androgen-insensitive prostate cancer (PCa) cells and silence of PLK1 promotes necroptosis-induced cell death in LNCaP-AI cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, knockdown of PLK1 resulted in decreased clonal survival, cell cycle arrest, and apoptosis in melanoma cells. Su et al 42 reported that higher PLK1 levels were associated with worse OS and disease-free survival (DFS), which is consistent with our results. In addition, Deeraksa et al 45 demonstrated that PLK1 expression is elevated in androgen-insensitive prostate cancer (PCa) cells and silence of PLK1 promotes necroptosis-induced cell death in LNCaP-AI cells.…”
Section: Discussionsupporting
confidence: 93%
“…Again, the synergistic effect was due to cell cycle arrest and greater induction of apoptosis. Su et al found that the expression of PLK1 and NOTCH was associated with poor overall and disease-free survival in melanoma, and the combination of BI6727 with the NOTCH inhibitor MK0752 resulted in a synergistic antiproliferative response in BRAF mutated, BRAF and TP53 mutated, and NRAS mutated melanoma cells ( 170 ).…”
Section: Plk1 Inhibition Combination Therapiesmentioning
confidence: 99%
“…Pathria et al [ 61 ] demonstrated that concomitant inhibition of AURKA/MEK might overcome resistance in NRAS -mutated melanomas, and Posch et al [ 62 ] reported that combination of MEK and PLK1 inhibitors suppresses proliferation of NRAS mutant melanoma cells in vitro and in vivo. In addition, it was revealed that PLK1 and NOTCH inhibitors had synergistic antiproliferative effect on multiple human melanoma cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%